Rekonstruksi Penyelesaian Sengketa Pemilu dan Paradigma Hakim dalam Putusan MK Nomor 2/PHPU.PRES-XXII/2024 - Aprilian Sumodiningrat (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Disputes over General Election Results (hereinafter abbreviated as PHPU) are dispute resolutions in the Constitutional Court based on the authority regulated in Law Number 7 of 2017 concerning Elections and Law Number 24 of 2003 concerning the Constitutional Court. There are fundamental problems in PHPU Presidential Elections regarding the resolution of violations that are structured, systematic, and massive. This study has conclusions, namely: First, the majority of judges have a fairly moderate view in viewing the position of the Constitutional Court to examine and prosecute violations of a TSM nature. However, all three constitutional judges have a dissenting opinion that uses the original intent method of interpretation in interpreting the authority. Second, there needs to be an expansion of the meaning of structured, systematic, and massive violations, and regarding time limits in PHPU in the Constitutional Court to produce substantive justice.